2016
DOI: 10.21512/bbr.v7i3.1499
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Point of View in Green Accounting

Abstract: The purpose of this research was to find out the influence of view attention, responsibility, reporting accounting environment, and audit environment to see the importance of green accounting on employees who worked in Tangerang related to the problem of the environment in the company. The research population consisted of all employees of the company. The eligible questionnaires were given to 108 respondents. Data collection was using questionnaires. The data were analyzed using the regression test with analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
1
3
1
1
Order By: Relevance
“…Therefore, it is important to plan better by combining different strategies in the implementation. The results of this study contradict the research conducted that green accounting has a significant impact on environmental performance [38], which in turn will have an impact on improving company finances [39,40].…”
Section: Figure 1 Path Analysis Discussioncontrasting
confidence: 99%
“…Therefore, it is important to plan better by combining different strategies in the implementation. The results of this study contradict the research conducted that green accounting has a significant impact on environmental performance [38], which in turn will have an impact on improving company finances [39,40].…”
Section: Figure 1 Path Analysis Discussioncontrasting
confidence: 99%
“…Based on the results of hypothesis testing conducted, it is known that the implementations of recycled materials, renewable energy, and green cost allocation have a positive effect on improving environmental performance mining and energy companies in Indonesia. This result is in accordance with Marota (2017), Hendratno (2016), and Khoirina (2016. This result is also consistent with the legitimacy theory.…”
Section: Resultssupporting
confidence: 91%
“…The results of Khoirina (2016) and Khoiruman and Haryanto (2017) explained that disclosure of environmental costs to management had a positive effect on environmental performance. The results of similar studies were also found related to the application of green accounting to improving environmental performance (Hendratno, 2016).…”
Section: Introductionmentioning
confidence: 56%
“…Teori tersebut mendukung adanya penyampaian atas laporan pertanggungjawaban sosial dan lingkungan. Legitimacy theory memuat pemangku kepentingan perlu memberikan legitimasi kepada perusahaan dan juga perusahaan dapat membangun citranya kepada pemangku kepentingan (Hendratno, 2016). Perusahaan harus memastikan bahwa operasional usahanya berjalan dalam batas norma dan nilai pada lingkungan masyarakat dimana perusahaan berada, sehingga aktivitas operasional perusahaan dapat dilegitimasi oleh pihak luar.…”
Section: Pembahasan 1 State Of the Artunclassified